2020
DOI: 10.1002/jbmr.3966
|View full text |Cite
|
Sign up to set email alerts
|

Ovariectomy Activates Chronic Low-Grade Inflammation Mediated by Memory T Cells, Which Promotes Osteoporosis in Mice

Abstract: The loss of estrogen (E2) initiates a rapid phase of bone loss leading to osteoporosis in one‐half of postmenopausal women, but the mechanism is not fully understood. Here, we show for the first time how loss of E2 activates low‐grade inflammation to promote the acute phase of bone catabolic activity in ovariectomized (OVX) mice. E2 regulates the abundance of dendritic cells (DCs) that express IL‐7 and IL‐15 by inducing the Fas ligand (FasL) and apoptosis of the DC. In the absence of E2, DCs become long‐lived,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 137 publications
(241 reference statements)
1
48
0
Order By: Relevance
“…These findings in the T cell–deficient mice are surprising and seem to be distinct to disuse bone loss and to contrast the role of T cells reported in nearly all local and systemic conditions associated with bone loss. For example, T cells have been proposed to be instigators of bone damage in rheumatoid arthritis, adjuvant arthritis, alveolar gingivitis and periodontal diseases, inflammation, lipid‐induced bone loss, Crohn's disease, irritable bowel disease, hyperparathyroidism, and estrogen deficiency 13–27 . Consistently, pharmacologic suppression or depletion or genetic ablation of T cells attenuated the disease‐specific bone loss 13–27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings in the T cell–deficient mice are surprising and seem to be distinct to disuse bone loss and to contrast the role of T cells reported in nearly all local and systemic conditions associated with bone loss. For example, T cells have been proposed to be instigators of bone damage in rheumatoid arthritis, adjuvant arthritis, alveolar gingivitis and periodontal diseases, inflammation, lipid‐induced bone loss, Crohn's disease, irritable bowel disease, hyperparathyroidism, and estrogen deficiency 13–27 . Consistently, pharmacologic suppression or depletion or genetic ablation of T cells attenuated the disease‐specific bone loss 13–27 .…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, several investigations identified T cells as major promoters of bone damage in diverse disease conditions and models, and that pharmacologic T cell suppression or depletion, or genetic ablation attenuates the disease‐specific bone loss 13–27 . Importantly, studies performed on humans and mice demonstrated reduced T cell number, T cell suppression, 28–32 or the presence of autoreactive T cells after SCI 33,34 .…”
Section: Introductionmentioning
confidence: 99%
“…However, an important link between estrogen loss, T-cell-dependent inflammation, and osteoporosis has been unraveled only recently. Cline-Smith et al for the first time described a molecular mechanism by which estrogen loss promotes a low-grade inflammation by T-cells during the acute phase of bone loss in ovariectomized mice (Cline-Smith et al, 2020[ 29 ]). They provide data suggesting a central role of bone marrow dendritic cells (BMDCs) in the induction of proinflammatory cytokines producing T-cells.…”
Section: Pathophysiology Of Osteoporosismentioning
confidence: 99%
“…IL-7 and IL-15, in turn, induces antigen-independent production of IL-17A and TNF in a subset of memory T cells (T MEM ). Further, a crucial role of the suggested pathway in OVX associated bone loss was confirmed by showing that T-cell-specific ablation of IL15RA prevented IL-17A and TNF expression and an increase in bone resorption or bone loss after OVX (Cline-Smith et al, 2020[ 29 ]). Interestingly, the authors speculate that a crucial role of the activation of T MEM in postmenopausal bone loss may provide an explanation for varying susceptibilities to develop osteoporosis within a population.…”
Section: Pathophysiology Of Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation